ESTIMULACIÓN TEMPRANA Y SU INFLUENCIA EN EL DESARROLLO MOTRIZ DE LOS NIÑOS DEL SEGUNDO AÑO DE EDUCACIÓN GENERAL BÁSICA DE LA UNIDAD EDUCATIVA “POTOSI” - PAREDES ANGULO KAREN KATHERINE (2024)
The study was based on determining how early stimulation influences the development of motor skills of children in the second year of basic general education in the “Potosí” Educational Unit; in addition, a significant deficit in early stimulation and its impact was identified, in the motor development of students. This problem is exacerbated by children's increasing exposure to electronic devices and sedentary lifestyles, which negatively affects their motor development. The study methodology used a mixed approach, with a non-experimental design based on field research to understand the present phenomena. The results showed that only 14% of the children were able to solve a puzzle without help, while 24% succeeded almost always and 38% were never able to solve it alone. These data indicate problems in fine motor skills and suggest a need for structured support and specific strategies to improve these skills. In the conclusions, the importance of early stimulation activities was highlighted, especially those focused on collective games and coordination exercises, which are essential for the development of motor skills. The implementation of these activities has proven to be effective in fostering cooperative and social skills, underscoring the need for a comprehensive program that addresses both the physical and social aspects of child development.